Clean-Development Investments: An Incentive-Compatible CGE Modelling Framework - Christoph Böhringer; Thomas F. Rutherford; Marco Springmann (University of Oldenburg, Department of Economics, 2013)
The Clean Development Mechanism (CDM) established under the Kyoto Protocol allows industrialized Annex I countries to offset part of their domestic emissions by investing in emissionsreduction projects in developing non-Annex I countries. We present a novel CDM modelling framework which can be used in computable general equilibrium (CGE) models to quantify the sector-specific and macroeconomic impacts of CDM investments. Compared to conventional approaches that mimic the CDM as sectoral emissions trading, our framework adopts a microeconomically consistent representation of the CDM incentive structure and its investment characteristics. In our empirical application we show that incentive compatibility implies that the sectors implementing CDM projects do not suffer, and that overall cost savings from the CDM tend to be lower than suggested by conventional modelling approaches.
Keywords: C68; Q58; 330; Clean Development Mechanism; Computable General Equilibrium Modeling; Clean Development Mechanism; Umweltschutzinvestition; Ökonomischer Anreiz; Allgemeines Gleichgewicht; Theorie